2002
DOI: 10.1177/000331970205300312
|View full text |Cite
|
Sign up to set email alerts
|

Complete Heart Block in a Patient with Wegener's Granulomatosis in Remission

Abstract: Wegener's granulomatosis is a systemic inflammatory disorder of unknown cause that usually affects the upper and lower respiratory tracts as well as the kidney. Cardiac involvement is rare, although electrocardiographic abnormalities, coronary artery vasculitis, cardiac arrhythmias, and myocardial infarction have been reported in the literature. A 27-year-old female patient with Wegener's granulomatosis in remission is described in whom complete heart block developed in the 13th month of treatment with cycloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Forstot et al [7]reported conduction system granulomata in 17% of WG patients, and arteritis of the blood supply to the atrioventricular node in 11% of cases. Several cases of high-grade atrioventricular block, including complete heart block, have been reported in the literature [4, 7, 11, 40, 41, 42, 43, 44]. Notably, the block may be reversible and responsive to intensification of the pharmacological therapy for WG.…”
Section: Conduction Disorders and Arrhythmiasmentioning
confidence: 99%
“…Forstot et al [7]reported conduction system granulomata in 17% of WG patients, and arteritis of the blood supply to the atrioventricular node in 11% of cases. Several cases of high-grade atrioventricular block, including complete heart block, have been reported in the literature [4, 7, 11, 40, 41, 42, 43, 44]. Notably, the block may be reversible and responsive to intensification of the pharmacological therapy for WG.…”
Section: Conduction Disorders and Arrhythmiasmentioning
confidence: 99%
“…Since then, there have only been 13 cases previously reported in the published literature and all but one case was associated with systemic disease (Table 1) [1,[3][4][5][6][7][8][9][10][11][12][13][14]. Complete AV block was present at disease onset in 50% and in 70% by one year.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotising angiitis and severe granulomatous inflammatory foci affected the common bundle of His and right bundle branch in addition to the myocardium [32]. Suleymenlar et al [33] report a case of patients with completed heart block due to GPA. Inflammation near the atrioventricular (AV) node was seen on computerised tomography (CT) and cardiac MRI, but also was confirmed by a myocardial perfusion scan with gallium [33].…”
Section: Cardiac Manifestation In Granulomatosis With Polyangiitismentioning
confidence: 99%
“…Suleymenlar et al [33] report a case of patients with completed heart block due to GPA. Inflammation near the atrioventricular (AV) node was seen on computerised tomography (CT) and cardiac MRI, but also was confirmed by a myocardial perfusion scan with gallium [33].…”
Section: Cardiac Manifestation In Granulomatosis With Polyangiitismentioning
confidence: 99%